Implantation site-dependent differences for tracheal regeneration with induced pluripotent stem cells (iPS cells). (April 2013) - Imaizumi, Mitsuyoshi; Nomoto, Yukio; Sugino, Takashi; Otsuki, Koshi; Omori, Koichi
Abstract Conclusion: The histological findings and quantitative measurements demonstrated that there were differences in teratoma formation according to the site of implantation. Elucidating the mechanisms of the teratoma formation caused by the site of implantation moves the field another step closer to clinical use of induced pluripotent stem (iPS) cells for tracheal regeneration. Objectives: Our previous study demonstrated the potential for iPS cells to be used as a new cell source for tracheal regeneration. However, teratoma formation remains a major problem. Implantation site-dependent differences in teratoma formation have been reported. In this study, the teratoma-forming propensity after implantation into tracheal defects and abdominal subcutaneous tissue was examined histologically and quantitatively. Methods: Mouse iPS cells were cultured in artificial material under various conditions. After cultivation in vitro, artificial materials with cultured iPS cells were then implanted into cervical tissue around tracheal defects and into abdominal subcutaneous tissue in nude rats. Teratoma formation was evaluated histologically and quantitatively with measurement of maximum diameter (MD). Results: Teratoma was observed in 10 of 11 rats with cervical tissue around tracheal defects and in 3 of 11 rats with abdominal subcutaneous tissue implants. The average MD was 5.36 mm in the trachea and 0.97 mm in the abdomen.